Relationship of Antimicrobial Cellular Immunity to Delayed Hypersensitivity in Listeriosis - Osebold, John W. (1974)
The relationship of antimicrobial cellular immunity to delayed hypersensitivity (DH) was studied in mice antigenically stimulated by living Listeria monocytogenes confined to diffusion chambers in peritoneal cavities or by subcutaneous inoculation of sublethal doses of the organism. Mice showed DH reactions when tested 6 days after inoculation, and reactions were positive for at least 90 days in some mice. DH also became established when the mice were stimulated by antigens diffusing from peritoneal chambers containing viable Listeria. Mice were categorized as DH positive or DH negative if they developed more or less than a 5% increase in foot volume 24 h after the injection of Listeria antigen. Some antigenically stimulated mice did not elicit the DH reaction. Consequently, the animals were arranged as immunized groups (DH positive and DH negative) and Listeria chamber implant groups (DH positive and DH negative). When challenged with L. monocytogenes, all four groups were significantly resistant as compared with controls. Thus, the in vivo tests for immunity and DH did not show direct correlation. The results suggested that antimicrobial cellular immunity can occur as a phenomenon independent of DH. Evidence for antimicrobial cellular immunity as the principle mechanism of resistance in murine listeriosis is discussed with consideration for possible heterogeneity of function by thymus-derived lymphocytes.